Predictors and long-term outcome of intracranial hemorrhage after thrombolytic therapy for acute ischemic stroke—A prospective single-center study - Fekete, Klára Edit; Héja, Máté; Márton, Sándor; Tóth, Judit; Harman, Aletta; Horváth, László; Fekete, István (Frontiers in Neurology, 2023)
Introduction: Acute ischemic stroke (AIS) is a potentially devastating disease with high disability and mortality. Recombinant tissue plasminogen activator (rt-PA) is an effective treatment with a 2-8% possible risk for symptomatic intracranial hemorrhage (sICH). Our aim was to investigate the risk factors and long-term clinical outcome of ICH in patients after rt-PA treatment. Methods: Consecutive patients with AIS, thrombolyzed at the Department of Neurology, University of Debrecen between January 1, 2004 and August 31, 2016 were enrolled prospectively. Risk factors, stroke severity based on the National Institute of Health Stroke Scale (NIHSS), functional outcome using modified Rankin-scale and mortality at one year were compared in patients with and without ICH following rt-PA treatment. We evaluated clinical characteristics and prognosis by hemorrhage type based on the Heidelberg Bleeding Classification. Descriptive statistics, χ2-test, Mann-Whitney U-test, ANOVA and Kruskal-Wallis-test, survival analysis, logistic regression were performed as appropriate. Results: Out of 1252 thrombolyzed patients, ICH developed in 138 patients, 37 (2.95%) being symptomatic. Mean ages in the ICH and non-ICH groups differed significantly (p=0.041). On- admission- and 24-hours-NIHSS after thrombolysis were higher in ICH patients (p<0.0001). Large vessel occlusion was more prevalent in ICH patients (p=0.0095). The ICH risk was lower after intravenous thrombolysis than intra-arterial or combined thrombolysis (p<0.0001). Both at 3 months and at one year the outcome was worse in ICH patients compared to the non-ICH group (p<0.0001). Mortality and poor outcome were more prevalent in all hemorrhage types with a tendency for massive bleeding associated with unfavorable prognosis. At 3 months with logistic regression model worse outcome was detected in patients with ICH after thrombolysis; at one year in patients with ICH after thrombolysis and smoking. Discussion: Older age, higher NIHSS, large vessel occlusion and intra-arterial thrombolysis may correlate with ICH. Unfavorable outcome is more common in ICH patients. Precise scoring of post-thrombolysis bleeding might be a useful tool in the evaluation of the patients’ prognosis. Our findings may help to identify predictors and estimate the prognosis of ICH in patients with AIS treated with rt-PA.